The relation between BRAFV600E mutation and clinicopathological characteristics of papillary thyroid cancer - Mehmet Celik; Buket Yılmaz Bulbul; Semra Ayturk; Yusuf Durmus; Hakan Gurkan; Nuray Can; Ebru Tastekin; Funda Ustun; Atakan Sezer; Sibel Guldiken (Medicinski glasnik, 2019)
Aim: BRAF mutation inhibits many tumour suppressor genes, increases pro-angiogenic molecules and reduces radioactive iodine uptake of tumour in papillary thyroid cancer (PTC), giving it more aggressive clinical characteristics. In this study, we aimed to evaluate the effect of BRAF V600E mutation on the clinicopathological features in patients with PTC. Methods: The laboratory and clinical findings of 256 PTC patients who were referred to our clinic between 2007 and 2017 were assessed. Subjects involved in the study were divided into two groups depending on the presence of BRAF V600E mutation. Results: BRAF V600E mutation testing gave positive results for 65 (25.4%) out of 256 patients. No significant correlation between BRAF V600E mutation, age and gender was detected. There was no difference between the groups in terms of tumour variant, tumour localization, tumour focality, and perineural invasion. In terms of histopathologic characteristics, presence of tumour capsular invasion (p=0.027), extrathyroidal extension (ETE) (p=0.002), absence of pathologically detected lymphocytic thyroiditis (p=0.006) and radio iodine I-131 treatment (p=0.001) were significantly higher in BRAF V600E (+) patients. During a followup period, four patients with BRAF V600E (+) and two patients with BRAF V600E (-) status underwent lateral neck dissection due to lymph node metastasis (p=0.01). Conclusion: The presence of BRAF V600E mutation was proved to be a poor prognostic factor. However, in order to further assess the prognostic effect of BRAF V600E mutation in this group of patients and particularly its effect on mortality, long term followup results must be evaluated.
Keywords: carcinoma; mutation; prognosis; thyroid neoplasms